Scoping Review: Dampak Penggunaan Kontrasepsi Hormonal Memengaruhi Disfungsi Seksual Pada Wanita - Yendena, Nelli; Anwar, Mochamad; Kartini, Farida; Astuti, Andari Wuri (Poltekkes Kemenkes Tanjung Karang, 2023)
Hormonal contraception is very effective in preventing pregnancy, but this contraception has various side effects. The objective is to determine how hormonal contraceptive use affects sexual dysfunction in women. In this research, the author follows the Arksey and O'Malley framework by identifying questions, identifying relevant articles, selecting and selecting papers, mapping data, discussing, concluding, and reporting results. The prism flowchart displays the flow of article searches on four databases: PubMed, Wiley, EBSCO, and ProQuest. This Scoping Review found 14 articles out of 1441 selected based on inclusion and exclusion criteria into three themes. Hormonal changes due to using Combined Hormonal Contraceptive (CHC) contraception negatively affect sexual life, namely increasing Sex Hormone Binding Globulin (SHBG) and decreasing free testosterone. The effect of hormonal contraceptives on female sexual dysfunction decreases libido, pleasure, orgasm, difficulty in lubrication, and vaginal dryness. Other factors affecting women's sexual function include age, education, premenopause, marital status, consumption of antidepressants, differences in partner age, income, and household harmony. CHC hormonal contraceptives cause sexual dysfunction in women due to decreased androgen hormones in the ovaries.